2017
DOI: 10.17511/ijmrr.2017.i10.05
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and cytological spectrum of lymphadenopathy: a window to preliminary diagnosis

Abstract: Introduction: Lymphadenopathy is a common clinical presentation of patients attending outdoor patient departments. The etiology varies with a wide spectrum ranging from inflammatory causes on one end to malignant on the other. In the present study, cytological and relevant histopathological diagnoses were done in 200 cases received in Department of Pathology. Aims and objectives: The present study aimed to find out the percentage of various lesions of lymph node and their prevalence according to age group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Similar pattern was observed in studies conducted by Ashwini et al and Pallavi SMS et al[4,6] Among the non-neoplastic lesions of lymph nodes, reactive lymphadenitis was frequently encountered. This resembles the studies concluded by Ashwini al, Damle R et al, Goyal S et al and Arun Roy et al[4,9,10,13] However, some studies, such as those directed by Shah B et, Pallavi SMS et al, Dr. Shubhangi V Agale et al and Gupta N et al concluded that tuberculosis is the most common among non-neoplastic lesions [3,6,8,11]. As for the site involvement by the disease our study shows reactive follicular hyperplasia to be involving mostly the cervical, mesenteric, inguinal, and iliac lymph node while metastasis was found mostly in axillary lymph node which was similar to the study done by Ashwini et al[4] in case of cervical lymph node but it differs in case of axillary, mesenteric, inguinal and iliac lymph nodes.This study also illustrates that among the neoplastic lesions, metastasis was the most common etiological factor.…”
supporting
confidence: 89%
“…Similar pattern was observed in studies conducted by Ashwini et al and Pallavi SMS et al[4,6] Among the non-neoplastic lesions of lymph nodes, reactive lymphadenitis was frequently encountered. This resembles the studies concluded by Ashwini al, Damle R et al, Goyal S et al and Arun Roy et al[4,9,10,13] However, some studies, such as those directed by Shah B et, Pallavi SMS et al, Dr. Shubhangi V Agale et al and Gupta N et al concluded that tuberculosis is the most common among non-neoplastic lesions [3,6,8,11]. As for the site involvement by the disease our study shows reactive follicular hyperplasia to be involving mostly the cervical, mesenteric, inguinal, and iliac lymph node while metastasis was found mostly in axillary lymph node which was similar to the study done by Ashwini et al[4] in case of cervical lymph node but it differs in case of axillary, mesenteric, inguinal and iliac lymph nodes.This study also illustrates that among the neoplastic lesions, metastasis was the most common etiological factor.…”
supporting
confidence: 89%
“…Hasil ini sesuai dengan beberapa penelitian yang menunjukkan bahwa sebagian besar kasus limfadenopati ditemukan pada rentang umur remaja awal hingga dewasa awal (15-35 tahun) dan perempuan menunjukkan persentase yang lebih tinggi dibandingkan dengan laki -laki. 5,6,[8][9][10][11][12][13][14][15] Tingginya temuan kasus pada perempuan dikaitkan dengan faktor, seperti perbedaan secara 2022; 1(2); 112-117 journal.unram.ac.id biologis, hormonal, sosial, dan tingkat imunitas yang rendah. Secara sosial pada negara berkembang, perempuan lebih rentan dikarenakan pada perempuan dengan status sosial ekonomi menengah ke bawah cenderung kurang memperhatikan masalah kesehatan dan jarang mengunjungi pelayanan kesehatan, serta perempuan yang berada dalam kelompok usia reproduksi cenderung belum stabil secara biologis dan hormonal.…”
Section: Karakteristik Respondenunclassified